A Au(i)-catalyzed hydrogen bond-directed tandem strategy to synthesize indeno-chromen-4-one and indeno-quinolin-4-one derivatives. Issue 77 (22nd August 2016) - Jiang, Chongguo; Xiong, Zhiling; Jin, Shengfei; Gao, Peng; Tang, Yingzhan; Wang, Yanshi; Du, Chuan; Wang, Xiaoyu; Liu, Yang; Lin, Bin; Liu, Yongxiang; Cheng, Maosheng
Abstract : A gold-catalyzed hydrogen bond-directed tandem cyclization strategy to synthesize indeno-chromen-4-one and indeno-quinolin-4-one derivatives has been developed. Abstract : A gold-catalyzed hydrogen bond-directed tandem cyclization strategy to synthesize indeno-chromen-4-one and indeno-quinolin-4-one derivatives has been developed. The hydrogen bond existing between the hydroxyl group (or the amide group) and the carbonyl group played an essential role in controlling the selectivity, which was confirmed by both experimental and theoretical evidence.